Alterations in Stress Parameters in Rats Housed in a Pyramid Model - Seasonal Variations - SUREKHA BHAT; GURUPRASAD RAO; K.DILIP MURTHY; P.GOPALAKRISHNA BHAT (International Journal of Pharma and Bio Sciences, 2010)
The space within the Great pyramid and its smaller replicas are believed to have healing powers due to the presence of cosmic and earth’s radiations which are influenced by seasons. The present study was done to determine if seasonal variations influence pyramid-mediated decrease in neuroendocrine and oxidative stress in rats. The experiment was conducted in Manipal, India (74º53’E, 12º55’N), through two seasons - hot (MarchMay, average temperature 33-35ºC , average humidity 60-70%) and cool (June-October, average temperature 26-29ºC, average humidity 80-90%). Wistar rats were divided into 4 groups, normal controls (NCH) and pyramid exposed in the hot season (PEH) and normal controls (NCC) and pyramid exposed in the cool season (PEC). Plasma cortisol was significantly lower in PEC as compared to NCC but not in PEH as compared to NCH rats. Erythrocyte TBARS was significantly lower and reduced glutathione and glutathione peroxidase activity were significantly higher in PEH and PEC than those in normal controls, statistical significance being more in the cool season for TBARS. SOD activity was significantly higher in PEH than in NCH, but not in PEC when compared to NCC. This shows that the effect of seasons and hence geographic location is a variable factor to be considered during pyramid therapy.